FisHiCal: an R package for iterative FISH-based calibration of Hi-C data - Shavit, Yoli (Bioinformatics, 2014)
Summary: The fluorescence in situ hybridization (FISH) method has been providing valuable information on physical distances between loci (via image analysis) for several decades. Recently, high-throughput data on nearby chemical contacts between and within chromosomes became available with the Hi-C method. Here, we present FisHiCal, an R package for an iterative FISH-based Hi-C calibration that exploits in full the information coming from these methods. We describe here our calibration model and present 3D inference methods that we have developed for increasing its usability, namely, 3D reconstruction through local stress minimization and detection of spatial inconsistencies. We next confirm our calibration across three human cell lines and explain how the output of our methods could inform our model, defining an iterative calibration pipeline, with applications for quality assessment and meta-analysis. Availability and implementation: FisHiCal v1.1 is available from http://cran.r-project.org/. Contact: ys388@cam.ac.uk Supplementary information: Supplementary Data is available at Bioinformatics online.